Efek Hipogykemia Pemberian Ekstrak Daun Johar Pada Tikus (Mus Musculus) Yang Di Induksi Dengan Streptozotosin - Dyah Ika Krisnawati (coba, 2012)
This thesis examines whether there johar leaf extracts hypoglycemic effect in mice made diabetic by induction streptozotosin. This type of research in this thesis is the experimental research, the design used was Pretest and Posttest Control Group Design. By using Federer formula, the number of samples are 24 mice were divided into 4 treatment groups: the 1st group as the control group was given CMC-na 0.5 %, the 2nd group was given a dose of 0.5 g/kgBW of johar extract / kg, the 3rd Group was given johar extract 1 g / kgBW, and the 4th group were given a dose of 2 g johar extract / kgBW. Examination of the blood glucose test was done using NESCO TEST. The results of post-treatment blood sugar outline obtained an increase in blood sugar in group 1 and group 2, while in group 3 and group 4 showed a decrease in blood sugar levels. Normality test results obtained p values> 0.05 is 1165, so it could be said to be normally distributed data. Homogeneity test results obtained p values> 0.05 is 0.106, so the data can be said to be homogeneous. Observations of blood glucose levels in all groups get p value> 0.05 that is 0.708 so it can be said from the time of reduction in blood sugar levels are not significant, while the value obtained from the group of p <0.05 is 0.020, Its can be significant. The conclusion of this study of johar leaf extract is not so useful when given to the type of insulin-dependent diabetes mellitus.